Examining a Sequential Mediation Model of Chinese University Students’ Well-Being: A Career Construction Perspective - Zhuang, Mingke; She, Zhuolin; Cai, Zijun; Huang, Zheng; Xiang, Qian; Wang, Ping; Zhu, Fei (Frontiers in Psychology, 2018)
Despite career construction theory attends to individual subjective career and provides a useful lens to study well-being, extant research has yielded limited insights into the mechanisms through which career construction variables influence individual well-being. To address this important gap, the present study examined a mediation model that links indicators of career adaptivity (big-five personality and approach/avoidance traits) to psychological well-being (psychological flourishing and life satisfaction) through career adaptability and in sequent meaning of life (presence of life meaning and search for life meaning) among a sample of Chinese university students (N = 165). The results of a two-wave survey study showed that career adaptability and presence of life meaning mediated the effects of openness to experience, consciousness, approach trait and avoidance trait on individual well-being in sequence. The results also showed that approach trait’s effect on presence of meaning was partially mediated by career adaptability; career adaptability’s effect on psychological flourishing was partially mediated by presence of meaning. These findings advance understanding of antecedents to individual well-being from a career construction perspective, and carry implications for career education and counseling practices.